2003
DOI: 10.1254/jphs.91.295
|View full text |Cite
|
Sign up to set email alerts
|

Special Sensitization Pattern in Adenosine-Induced Myocardial Responses After Thyroxine-Treatment

Abstract: Chronic thyroxine treatment reduces the susceptibility of atrial myocardium to adenosine. While the possible role of membrane adenosine receptors in this action is supported by several studies, the involvement of intracellular adenosine mechanisms has not been defined. The present experiments were carried out in electrically driven euthyroid and hyperthyroid guinea pig atrial myocardium. The extracellular and intracellular actions of adenosine were analyzed pharmacologically by the use of specific blockers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…In earlier studies, inhibition of nucleoside transport was found to augment the response to adenosine that is primarily reflected by a leftward shift (decreased EC 50 ) of the adenosine E/c curve (Szentmiklosi et al 1982;Gesztelyi et al 2003a). This phenomenon can be explained by the fact that, under well-oxygenated conditions, the net transmembrane adenosine transport is directed into the cardiomyocytes due to the rapid intracellular elimination of adenosine (Deussen et al 1999;Deussen 2000aDeussen , 2000b.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In earlier studies, inhibition of nucleoside transport was found to augment the response to adenosine that is primarily reflected by a leftward shift (decreased EC 50 ) of the adenosine E/c curve (Szentmiklosi et al 1982;Gesztelyi et al 2003a). This phenomenon can be explained by the fact that, under well-oxygenated conditions, the net transmembrane adenosine transport is directed into the cardiomyocytes due to the rapid intracellular elimination of adenosine (Deussen et al 1999;Deussen 2000aDeussen , 2000b.…”
Section: Discussionmentioning
confidence: 94%
“…Because NBTI strongly affects the fate of exogenous adenosine used to generate an E/c curve (Szentmiklosi et al 1982;Gesztelyi et al 2003a), adenosine could not be used as an agonist for the E/c curves essential for RRM (Karsai et al 2006). However, RRM enables replacement of a degradable agonist with a stable one (Gesztelyi et al 2004;Grenczer et al 2010aGrenczer et al , 2010b.…”
Section: Strategy Of the Mathematical Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of FSCPX and NBTI on the E / c curves of adenosine receptor agonists can be divided into three components: Effects mediated by influencing the interstitial level of endogenous adenosine (that were earlier attributed exclusively to NBTI [ 26 , 27 ]), effects mediated via affecting the interstitial level of exogenous adenosine (also ascribed to NBTI [ 28 ]) and effects resulted from the permanent inactivation of a fraction of the A 1 receptor population (attributed to FSCPX [ 11 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid state influences several regulatory mechanisms including functions of the A 1 receptor (for a brief review, see Gesztelyi et al 2012 ). Among others, thyroid hormones (T 3 , T 4 ) markedly reduce the direct negative inotropic effect (decrease of the contractile force without prior positive inotropic stimulation exerted by another agent) of A 1 receptor agonists (Szentmiklosi et al 1992 ; Kaasik et al 1994 ; Gesztelyi et al 2003a ). Hyperthyroidism is a pathological condition that, by upregulating a wide range of metabolic processes, raises the oxygen and nutrient consumption in the tissues and thus increases the work of the heart (Cini et al 2009 ; Nabbout and Robbins 2010 ).…”
Section: Introductionmentioning
confidence: 99%